Paraglacial Rock Slope Adjustment Beneath a High Mountain Infrastructure—The Pilatte Hut Case Study (Écrins Mountain Range, France) - Duvillard, Pierre-Allain; Ravanel, Ludovic; Deline, Philip; Dubois, Laurent (Frontiers in Earth Science, 2018)
Landslides triggered by shrinking glaciers are an expected outcome of global climate change and they pose a significant threat to inhabitants and infrastructure in mountain valleys. In this study we document the rock slope movement that has affected the Pilatte hut (2,572 m a.s.l.) in the Écrins range (French alps) since the 1980s. We reconstructed the geometry of the unstable rock mass using Terrestrial Laser Scanning and quantified the unstable volume ( 400,000 m3). Field observations and annual crack surveys have been used to identify the dynamics of past movements. These movements initiated in the late 1980s and have accelerated since 2000. The current trend seems to be toward a relative stabilization. Reconstruction of the glacier surface using past images taken since 1960 and “Structure from Motion” photogrammetry showed that the glacier probably applied stresses to the rock slope during its short-lived advance during the 1980s, followed by debuttressing caused by rapid surface lowering until the present day. The relationship between observed crack propagation and glacier surface change suggests that the rock slope instability is a paraglacial response to glacier surface changes, and highlights that such responses can occur within a decade of glacier change.